2020
DOI: 10.1097/qai.0000000000002333
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Three- Versus Six-Monthly Dispensing of Antiretroviral Treatment (ART) for Stable HIV Patients in Community ART Refill Groups: A Cluster-Randomized Trial in Zimbabwe

Abstract: Introduction: Multimonth dispensing (MMD) of antiretroviral treatment (ART) aims to reduce patient-related barriers to access long-term treatment and improve health system efficiency. However, randomized evidence of its clinical effectiveness is lacking. We compared MMD within community ART refill groups (CARGs) vs. standard-of-care facility-based ART delivery in Zimbabwe. Methods: A three-arm, cluster-randomized, pragmatic noninferiority trial was performed. Thirty health care facilities and associated CARGs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 23 publications
7
79
0
Order By: Relevance
“…This is the first study reporting 24-month outcomes. Our outcomes are consistent with interim 12-month outcomes in two recently published cluster randomized trials in Zimbabwe [31] and Lesotho [30] that showed non-inferior retention in community-based DSDs receiving six-monthly refills, compared to three-monthly facility controls. VL suppression was non-inferior in the Lesotho study [30], but not the Zimbabwean study, possibly because of low VL completion rates [31].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This is the first study reporting 24-month outcomes. Our outcomes are consistent with interim 12-month outcomes in two recently published cluster randomized trials in Zimbabwe [31] and Lesotho [30] that showed non-inferior retention in community-based DSDs receiving six-monthly refills, compared to three-monthly facility controls. VL suppression was non-inferior in the Lesotho study [30], but not the Zimbabwean study, possibly because of low VL completion rates [31].…”
Section: Discussionsupporting
confidence: 89%
“…Our results add to the growing literature showing good retention and clinical outcomes associated with extended ART dispensing intervals [30,31,[46][47][48]. This is particularly important at a time when countries will be considering whether to continue or reverse six-monthly ART refills provided during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Evidence from two choice experiments in this synthesis showed a strong relative preference for three monthly as opposed to one monthly refills compared with other service attributes, and a further three experiments demonstrate no differences in preference for longer refill intervals when compared with 3-month prescribing. This mirrors findings from observational studies and trials which demonstrate improved retention with three or six monthly versus one monthly ART refill frequency [33,35] but minimal difference in HIV treatment outcomes for three versus six monthly refill comparisons [36,37]. Efforts should be made to optimize drug supply chains and pharmacy storage capacity to ensure that all settings are able to provide at minimum 3-month refills and where possible longer drug supplies should be considered [38].…”
Section: Discussionsupporting
confidence: 63%